2021
DOI: 10.24953/turkjped.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of critically ill children transported by ambulance in a Turkish prehospital system: a multicenter prospective cohort study

Abstract: Background. The most underdeveloped area in the care of critically-ill-children (CIC) is the prehospital period. Appropriate prehospital assessment and life-saving-interventions (LSI) of this population are challenging and require dedicated resources to ensure the best outcomes. We aimed to determine the characteristics and outcomes of CIC transported to the Turkish Pediatric Emergency Departments (EDs). The frequency and distribution of LSI administered by prehospital providers on route and in the EDs were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this study, the rate of patients admitted to pediatric ED by 112 ambulances was found as 1.3% annually.This rate was 5% and 7% in two different hospitals in the USA [6]. In a multicenter study from 9 hospitals in Turkey, it was reported that total number of children arriving to a pediatric ED by an ambulance was 2094 [7]. In our study, 3883 visits to a single center within a year indicated the workload of Kayseri City Hospital in the medical environment of Turkey.…”
Section: Discussionmentioning
confidence: 49%
“…In this study, the rate of patients admitted to pediatric ED by 112 ambulances was found as 1.3% annually.This rate was 5% and 7% in two different hospitals in the USA [6]. In a multicenter study from 9 hospitals in Turkey, it was reported that total number of children arriving to a pediatric ED by an ambulance was 2094 [7]. In our study, 3883 visits to a single center within a year indicated the workload of Kayseri City Hospital in the medical environment of Turkey.…”
Section: Discussionmentioning
confidence: 49%
“… 62 Similarly, a study in Turkey reported a higher short-term mortality rate among pediatric emergencies if the ambulance was staffed by only paramedics. 65 …”
Section: Resultsmentioning
confidence: 99%
“…57,58,63 Only a minority of ambulances across LMICs were physicianstaffed or had Basic Life Support (BLS)-trained personnel. [64][65][66][67][68] A study conducted among cardiac emergency cases in Iran found a lower death rate when transported by EMS. 62 Similarly, a study in Turkey reported a higher short-term mortality rate among pediatric emergencies if the ambulance was staffed by only paramedics.…”
Section: Status Of Prehospital Emergency Care Servicesmentioning
confidence: 99%
See 1 more Smart Citation